The Weight of Seedlings Differs on the Growth of Sargassum sp. - Ifla Afifilah; Nunik Cokrowati; Nanda Diniarti (Jurnal Biologi Tropis, 2021)
Sargassum sp. is a brown alga containing alginate and iodine and is used in the food, pharmaceutical, cosmetic and textile industries. Cultivation of Sargassum sp. has not been carried out, but it needs efforts to be cultivated so that its availability is sustainable. This study aims to determine the growth of Sargassum sp. cultivated with different seed weight in the longline method. This research was conducted from December 2020 to January 2021, in the waters of Ekas Bay, Ekas Buana Village, Jerowaru District, East Lombok Regency. This research was conducted using experimental methods and using the weight difference treatment of the seeds of Sargassum sp. Cultivation was carried out for 30 days. The experimental design used in this study was a completely randomized design consisting of 5 treatments and 4 replications. The treatments were treatment A (seeds weighing 25 g), B (seeds weighing 50 g), C (seeds weighing 100 g as a control), D (seeds weighing 150 g) and E (seeds with a weight of 150 g). weight 200 g). The results showed that E treatment showed the best growth results with the growth parameters measured were absolute growth, specific growth, number of leaves and number of fruits. This study concludes that different seed weight has a significant effect on the growth of seaweed Sargassum sp. with the longline method with the best seed weight in this study was the E treatment (200 g) with an absolute growth of 437.5 g, a specific growth rate of 21.50%, 4999 fruit numbers, and 3614 leaves.